Charge-trap flash memory using zirconium-nitride-based memristor switches. (8th October 2015) - Kim, Hee-Dong; Kim, Kyeong Heon; An, Ho-Myoung; Kim, Tae Geun
Abstract: Charge-trap flash (CTF) memory using a zirconium nitride (ZrN)-based memristor switch (MRS) is demonstrated for next-generation nonvolatile memory. This device consists of a metal/MRS/nitride/oxide/silicon (M/MRS/N/O/S) structure so that electrical transport via the ZrN-based MRS layer can be utilized. Compared to previous oxide materials used as conduction paths, the proposed CTF device with a ZrN-based MRS exhibits a faster program/erase switching speed (20 ns/7 ns), along with comparable endurance and retention properties.